REGULASI HORMONAL DALAM KESEIMBANGAN CAIRAN DAN ELEKTROLIT SELAMA LATIHAN - YULIASTRID, DITA (Arena, 2010)
Abstract: Aldosterone,renin, angiotensin and ADH all increase substantially during exercise, because they are involved in the regulation and control of electrolytes, water metabolism, and fluid volume. The mehanism for the increased ADH and aldosterone hormone concentration with exercise are unknown but they are related to the increased osmotic activity of the blood that occurs as plasma volume is decreased during exercise.Vasopresin or ADH increased retention of water by kydneys during severe exercise, especially when the exerciser is dehydrated. Plasma aldosterone concentrations rise progresively during exercise of increasing intensity with peak aldosterone levels of up to 6 times the resting value having been reported. The mechanism underlying the aldosterone response to exercise apparently involves the renin-angiotensin system, because the concentrations of both renin and angiotensin also show substantial rises in plasma with exercise. Key words : hormone, fluid-electrolyte, exercise